(untitled) (Fiep Bulletin - online, 2015)
Obesity is a chronic metabolic condition associated with numerous morbidities including cardiovascular disease, insulin resistance, hypertension and infertility. Obesity is directly associated with increased activity of renin angiotensin system (RAS). The peptide Angiontensin II is well known for his involvement in the control of body fluid and cardiovascular homeostasis and also has impact on the control of reproduction. Losartan is an antagonist of the Ang II AT1 receptor and its administration can be beneficial in order to reduce infertility resulting from obesity. The aim of this study was to evaluate the effect of blocking the AT1 Ang II receptor antagonists on spermatogenesis and sperm morphology in obese Wistar rats. After weaning male rats were treated with standard diet (CTL) or with cafeteria diet (CAF). At 70 days old, the cafeteria group was divided into two subgroups, half receiving water by daily gavage (CAF) and the other half receiving losartan by gavage, 30 mg/kg of body weight / day (CAF + LOS); the control group received water by daily gavage. The spermatogenic processes and morphology, as well as the weights of the reproductive organs and of retroperitoneal and perigonadal fats were analyzed. The cafeteria diet induced obesity by increasing the absolute and relative weight of the fats and altered the morphology of the head and tail of the sperm of the rats. Losartan did not reverse the changes caused by excess body fat in the morphology of spermatozoa. Other parameters were not altered by the cafeteria diet alone or combined with losartan. The lack of effect of losartan on all evaluated reproductive parameters may signal that he has no mediating effect thereof.